2021
DOI: 10.1107/s1600577521004033
|View full text |Cite
|
Sign up to set email alerts
|

XANES reflects coordination change and underlying surface disorder of zinc adsorbed to silica

Abstract: Zinc K-edge X-ray absorption near-edge structure (XANES) spectroscopy of Zn adsorbed to silica and Zn-bearing minerals, salts and solutions was conducted to explore how XANES spectra reflect coordination environment and disorder in the surface to which a metal ion is sorbed. Specifically, XANES spectra for five distinct Zn adsorption complexes (Znads) on quartz and amorphous silica [SiO2(am)] are presented from the Zn–water–silica surface system: outer-sphere octahedral Znads on quartz, inner-sphere octahedral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…According to the Zn K-edge X-ray absorption near-edge structure (XANES), Zn in CP std -ZnZrO x is in the approximate 2+ state (Figure S2a). Comparing the K-edge energy position ( E 0 ) and normalized edge absorbance of tetrahedral and octahedral Zn 2+ compounds (Figure S2b), we found that tetrahedral Zn 2+ species generally have lower E 0 and absorbance of edge than octahedral Zn 2+ species. Notably, Zn in CP std -ZnZrO x shows an intermediate value of E 0 and edge absorbance (9663 eV and 1.65, respectively) compared to other standard Zn compounds, indicating that the chemical state of Zn is intermediate between tetrahedral and octahedral.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Zn K-edge X-ray absorption near-edge structure (XANES), Zn in CP std -ZnZrO x is in the approximate 2+ state (Figure S2a). Comparing the K-edge energy position ( E 0 ) and normalized edge absorbance of tetrahedral and octahedral Zn 2+ compounds (Figure S2b), we found that tetrahedral Zn 2+ species generally have lower E 0 and absorbance of edge than octahedral Zn 2+ species. Notably, Zn in CP std -ZnZrO x shows an intermediate value of E 0 and edge absorbance (9663 eV and 1.65, respectively) compared to other standard Zn compounds, indicating that the chemical state of Zn is intermediate between tetrahedral and octahedral.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Zn K-edge X-ray absorption near-edge structure (XANES), Zn in CPstd-ZnZrO x is in the approximate 2+ state (Figure S2a). Comparing the K-edge energy position (E 0 ) and normalized edge absorbance of tetrahedral and octahedral Zn 2+ compounds (Figure S2b), 45 we found that tetrahedral Zn 2+ species generally have lower E 0 and absorbance of edge than octahedral Zn CO 2 -to-MeOH Performance of ZnZrO x Catalysts. The CO 2 hydrogenation performance of ZnZrO x catalysts was measured at 320 °C, 5 MPa, CO 2 /H 2 /Ar = 24/72/4, and 24,000 cm 3 g cat.…”
Section: Synthesis Of Znzro X Catalysts By Varying Synthesismentioning
confidence: 92%
See 1 more Smart Citation
“…23,24 Local bonding geometry affects electronic structure, which affects the shape and location of K-edge spectra without altering oxidation states. [33][34][35][36][37][38][39] For example, the Zn(II) K-edge is shifted and distorted by local geometry when ions adsorbed to silica and quartz, 33 changes in coordination symmetry for Cu(II) ions distort the rising edge portion of spectra, 37 and even the fluorine K-edge spectra show variations with changes in local symmetry in the highly-ionic alkali and alkali earth salts. 38 Simple analysis of edge location cannot differentiate between the two possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…The XANES spectra were collected from ~10 or more regions (Zn-containing particles) of sample filters to evaluate variations in Zn speciation, encompassing particles with variable Zn concentrations and the diversity of pZn species found in the filter samples. Because Zn-XANES spectra are highly sensitive to Zn speciation, we compiled more than 50 Zn reference spectra of standard compounds, whose Zn coordination is well understood ( 25 29 ) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%